PERBEDAAN HUBUNGAN FUNGSI SENSORIS DAN CORE STABILITY TERHADAP KESEIMBANGAN DINAMIS PADA ANAK USIA 3-5 TAHUN DI AL-FATIH CENTER TANGERANG - Rovika Trioclarise; Miratiani Sitompul; Ahmad Syakib (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Introduction: Problems with balance can occur in early childhood because of problems in sensory function and weak core stability. The purpose of this study was to determine the differences in the relationship of sensory function and core stability on dynamic balance in children aged 3-5 years at Al-Fatih Center Tangerang in 2022. Methods: This type of research is observational with a cross sectional study design. The population were all children aged 3- 5 years at Al-Fatih Center Tangerang with a sample of 82 people. Tests were conducted using Sensory Processing Measure-Preschool to determine sensory function, Supine Flexion to determine core stability, Pediatric Balance Scale to determine children's dynamic balance. Result: The relationship between sensory function and core stability on dynamic balance (p- value 0.000) and and standardized coefficients beta on core stability is 0.312. Conclusion: Core stability is more influential than sensory function on dynamic balance.